2017
DOI: 10.1038/s41598-017-03737-2
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Biphasic Hydroxylapatite-Beta Magnesium Tricalcium Phosphate in Heat Treated Salmonid Vertebrae

Abstract: Ichthyoarchaeological evidence is uncommon at ancient hunter-gatherer sites from various regions and timeframes. This research contributes to the development of microarchaeological techniques useful for identifying fishing economies in situations where classifiable bones are unavailable. Specifically, traces of heat altered bone mineral in domestic hearths are expected to provide markers for discarded fish remains. We used a series of laboratory incineration experiments to characterize the mineralogy of burned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…2B–D ; Supplementary Information 2A). The formation of these minerals primarily owes to the Ca 2+ deficient, Mg 2+ rich nature of the hydroxylapatite (HAp: Ca 10 (PO 4 ) 6 (OH) 2 ) mineral in these bones 1630 . This finding demonstrated that new minerals formed in burned Atlantic salmonid bones can preserve in acidic northern archaeological contexts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2B–D ; Supplementary Information 2A). The formation of these minerals primarily owes to the Ca 2+ deficient, Mg 2+ rich nature of the hydroxylapatite (HAp: Ca 10 (PO 4 ) 6 (OH) 2 ) mineral in these bones 1630 . This finding demonstrated that new minerals formed in burned Atlantic salmonid bones can preserve in acidic northern archaeological contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Dozens of black, brown, white, and grey particles of what appeared to be bone were selected for mineralogical analysis by FTIR. Several black bone particles (0.5–2 mm in diameter) were found to contain both WH and crystalline HAp (Figs 3, S2, S3D and Supplementary Information 2C) 1619,30 . HAp crystallinity could not be assessed using the infrared splitting factor (IRSF), as the presence of WH bands distorted the phosphate (PO 4 ) v 4 band required to make the calculation (see Materials and Methods and Supplementary Information 2B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A razão molar de Ca/P, calculada através do percentual atômico (Tabela 1), foi de 1,52. Segundo a literatura, o TCP-β apresenta razão molar de 1,50 [30,31,32,33,34], o que corrobora a formação da amostra desejada.…”
Section: Figuraunclassified